Exploration Practice Management Green Quality and Its Impact to Sustainability - Supriyono, Supriyono; Suryanto, Dwi; Purwanto, Yusup (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Study This aim For explore practice management quality green as well as analyze the impact to sustainability organization. Management quality green is approach strategic integration​ principle management quality with aspect environment use increase performance sustainable research​ This use approach qualitative with design studies case For get comprehensive understanding​ related implementation practice said. Informant in study This consists of on owner business as informant main, manager operations and employees as informant key, and customer as informant additional, selected purposively. The data collection technique was carried out through interview in-depth, observation, and documentation. Data analysis using technique analysis thematic through stages data reduction, data presentation, and data extraction conclusion . Research results show that practice management quality geen implemented through efficiency use source power , management waste sustainable use​ material friendly environment , as well as implementation standard operational based environmental factors​ supporters main covering commitment management , level awareness environment employees , and integration internal organizational policies . Implementation the give impact positive to improvement performance environmen, efficiency operational, as well as strengthening Power competitiveness and image organization. However Thus, there are a number of constraint in implementation, including limitations​ source power, lack of understanding technical, as well as Not yet optimally support policy external. Therefore that, is necessary synergy between organizations and stakeholders interest For strengthen implementation management quality green. Research This expected give contribution theoretical and practical in sustainability strategy development organization